Data and Mobility Transforming Information into Intelligent Traffic and Transportation Services. Proceedings of the Lakeside Conference 2010 - Düh, Julia; Hufnagl, Hartwig; Juritsch, Erhard; Pfliegl, Reinhard; Schimany, Helmut-Klaus.; Schönegger, Hans.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This volume of Advances in Soft Computing contains the accepted and outstanding papers presented at the Lakeside Conference 2010 in Carinthia, Austria. The topic of the Lakeside Conference 2010, Data and Mobility – Transporting Information into Intelligent Traffic and Transportation Services, was chosen to underline the importance of information and mobility in transport and to discuss current activities in this sector. The development of traffic management systems, under the influence of new technologies, is a fast-changing subject and needs experts to guide us in the right direction. Worldwide, a variety of solutions is being developed to make traffic management safer, more sustainable and efficient. The 18 papers published in this book represent the work of national and international companies, universities and research & development departments and reflect a number of current research streams. The articles cover significant recent developments in the field, both in terms of data and mobility, self-learning traffic monitoring systems, ETC-based traffic telematics solutions and naturalistic driving – a new method of data collection. The wide range of activities also contains reports offering viewpoints on cross-border issues such as transnational nowcasting systems or the comparison between the European and the American ITS system architecture. The organizers also took special care to include papers dealing with national and geographical characteristics, such as the standardized documentation of flood damage and winter maintenance management systems.
A Multimedia-Centric Quality Assurance System for Traffic Messages -- Autonomous Multi-sensor Vehicle Classification for Traffic Monitoring -- Concepts for Modeling Drivers of Vehicles Using Control Theory -- COOPERS: Driver Acceptance Assessment of Cooperative Services -- Developments within the Scope of the German Test Site for Road Weather Stations -- Documentation of Flood Damage on Railway Infrastructure -- ETC-Based Traffic Telematics -- Extraction of Visual and Acoustic Features of the Driver for Monitoring Driver Ergonomics Applied to Extended Driver Assistance Systems -- How Motorcycle Collisions Depend on Weather -- Integrated Nowcasting System for the Central European Area: INCA-CE -- Intelligent Transport System Architecture Different Approaches and Future Trends -- Looking into Detection, Model Results and Message Quality -- Maintenance Decision Support System (MDSS) ASFINAG / Austria -- METIS -- Naturalistic Driving -- Re-thinking Urban Mobility Services and Operations -- Road Weather Information Service in Finland -- Using Vehicles as Mobile Weather Platforms.
Keywords: Automotive engineering; Artificial intelligence; Computational intelligence; Automotive Engineering; Artificial Intelligence; Computational Intelligence